AYAM TALIWANG SEBAGAI WISATA KULINER UNGGULAN DI KOTA MATARAM LOMBOK NUSA TENGGARA BARAT - Insanaputra, Yanuar Satrhio (Kepariwisataan: Jurnal Ilmiah, 2020)
Taliwang chicken is food originating from Taliwang, West Sumbawa, West Nusa Tenggara, whose main ingredient is young free-range chicken. Young kampung chickens are grilled with typical Taliwang spices and are usually served with lombok specialties, such as pelecing. The obstacle that appears in making Taliwang chicken as a superior culinary in the city of Mataram is the lack of appreciation of the government in making regulations for the Taliwang chicken culinary. An example is the patenting of culinary names that have been handled by managers for a long time, but are still in process. Data collection methods used in this study were interviews, observation, documentation, and questionnaires. The data was analized in the form of SWOT Analysis. Keywords: Excelent Culinary, Taliwang Chicken, Mataram City